Retrospective Analysis of Seasonal Changes in Semen Analysis Parameters - Sinan Ates; Cem Yener; Mehmet Gurkan Arikan; Ersan Arda; Deniz Cokay; Koray Elter (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: Seasonal and environmental temperature changes may affect semen analysis results. This study aimed to evaluate the effect of seasonal changes on semen analysis parameters.